Bioengineered chitosan-iron nanocomposite controls bacterial leaf blight disease by modulating plant defense response and nutritional status of rice (Oryza sativa L.). (August 2022) - Ahmed, Temoor; Noman, Muhammad; Jiang, Hubiao; Shahid, Muhammad; Ma, Chuanxin; Wu, Zhifeng; Nazir, Muhammad Mudassir; Ali, Md. Arshad; White, Jason C.; Chen, Jianping; Li, Bin
Abstract: Rice production is severely affected by the bacterial pathogen, Xanthomonas oryzae pv. oryzae (Xoo), which causes bacterial leaf blight (BLB) disease. Nano-enabled strategies have recently attracted attention as a sustainable platform to improve crop nutrition and protection. Here, we report the bioengineering of chitosan-iron nanocomposites (BNCs) along with their in vitro and in vivo bactericidal activity against Xoo. In addition, the impact of BNCs on the endophytic microbiome of healthy and BLB diseased rice was evaluated using a high-throughput sequencing technique. The BNCs were spherically shaped with an average size of 86 nm. In vitro antibacterial assays showed that BNCs significantly inhibited biological functions of the pathogen ( viz., growth, motility, and biofilm formation) at 250 μg mL −1 concentration as compared with respective control. A greenhouse experiment demonstrated that foliar exposure to 250 mg·L −1 BNCs significantly reduced the BLB disease incidence (67.1%) through modulation of antioxidant enzymes viz., superoxide dismutase (49.2%), peroxidase (38.8%) and ascorbate peroxidase (53.4%); BNCs amendment also improved photosynthesis efficiency by promoting production of total chlorophyll (43.2%) and carotenoids contents (60.0%), and the nutritional profile of rice plants as compared with untreated diseased control. Moreover, BNCs-induced disease resistance response corresponded to an increase in transcript level of defense-related genes, such as OsPRs, OsSOD and OsAPX, in rice plants. High-throughput sequencing results revealed that BNCs amendment decreased the relative abundance of Xanthomonas (87.5%) by reshaping the phyllospheric and root-endophytic bacterial community of rice. In addition, BNCs increased the bacterial community diversity in healthy and diseased plants; significant increases in relative abundance of Ochrobactrum, Allorhizobium, Methylobacterium, Devosia, Pseudolabrys, Sphingomonas and Bradyrhizobium in BNCs-treated diseased and healthy plants was noted. These findings demonstrate that BNCs have potential to serve as non-toxic, sustainable and highly efficient alternative for plant disease management. Graphical Abstract: ga1 Highlights: Synthesis and characterization of bioengineered chitosan iron nanocomposites (BNCs) as a bactericidal agent. In vitro and in vivo antibacterial activity of BNC against rice pathogen Xanthomonas oryzae pv. oryzae (Xoo). Ultrastructure studies reveal the subcellular localization of BNCs within the rice leaf cells. High-throughput sequencing revealed the impact of BNCs on the rice endophytic microbiome. BNCs amendment significantly reduce the Xoo abundance and modulate the rice microbial community composition.